Functional outcome evaluation for plate fixation of calcaneum fracture - Mohd Ariffullah Ariffin (Kulliyyah of Medicine, International Islamic University Malaysia, 2019)
Objective: This study was designed to evaluate the functional outcome of the patient with closed displaced intraarticular calcaneum fractures treated with plate fixation. Methods: 26 cases of displaced intraarticular calcaneum fractures were treated surgically in Hospital Tengku Ampuan Afzan from January 2014 to January 2019. All patients followed-up with a minimum of 1 year and evaluated for quality of life (SF-36) and radiological (Böhler's angle) outcomes by a series of questionnaires and measurements. Result: There were 25 males (Sander classification type 2=7, Sander classification type 3=17, Sander classification type 4=1) and 1 female (Sander classification type 3=1). The average age was 42.8 years. The mode of fixation for all cases was using locking calcaneum plate. The cases were performed by Foot and Ankle trained surgeons. Extended lateral approach to the calcaneum was used in all cases. Patient was followed up a range of 1-3 years. On average, surgery was done 11 days post trauma. At the final follow-up visit, the mean QOL score (SF-36) was 55.9 and the mean for post-operative Böhler's angle was 22°. The correlation between SF-36 score and post-operative Böhler's angle was not significant, but shows positive and weak correlation exist between. The association between types of fracture (Sanders classification) to post-operative Böhler's angle was significant. Conclusion: Males formed a majority over females with an average age of 42.8 years old. Motor vehicle accident forms the leading cause of fractures. Closed fracture of calcaneus treated with plate fixation gives a good functional outcome by restoring the anatomical construction and Böhler's angle.